IMMUNOMODULATORY POTENTIAL OF ETHANOL EXTRACT OF HENNA LEAF (Lawsonia Inermis L.) AGAINST MACROPHAGE PHAGOCYTOSIS IN MALE MICE (Mus Musculus): EXTRACT OF HENNA LEAF - Purnamasari, Wa Ode Gustiani; Mulanna, Fauziah; Yuliastri, Wa Ode; Yuhadi, Asfani (STIKes Mandala Waluya Kendari, 2025)
Background: One of the herbal plants that can be used as an immunomodulator is henna leaves (Lawsonia inermis L.) that increase the function of the immune system. The purpose of this study was to determine the immunomodulatory potential of henna leaves on macrophage phagocytosis and to determine at what dose the ethanol extract of henna leaves has the potential for macrophage phagocytosis in male mice (Mus musculus). Methods: The type of research used is analytical research using administering ethanol extract of henna leaves on increasing macrophage phagocytosis in male mice (Mus musculus) induced by Staphylococcus aureus, and to determine which dose is more effective in increasing phagocytosis using the phagocytosis test. The analysis method uses the ANOVA Statistical Test and the LSD Post Hoc Test. Results: The study showed that the ethanol extract of henna leaves has an immunomodulatory effect based on the results of the One Way ANOVA statistical test and post hoc test (p-value <0.05). The dose of ethanol extract of henna leaves that has immunomodulatory potential is a dose of 100 mg/kgBW (34.33%), a dose of 200 mg/kgBW (46%), a dose of 300 mg/kgBW (74.66%) and a dose of 400 mg/kgBW (75.33%). Conclusion: The study conclude that Ethanol extract of henna leaves has mmunomodulatory potential by increasing macrophage phagocytosis activity in male mice. Ethanol extract of henna leaves which is effective as an immunomodulator is 400 mg/kgBW which has a higher percentage of macrophage phagocytosis activity value compared to other dose variations, and is approximately the same as the positive control this is due to the number of phagocytic cells that actively carry out phagocytosis and is expressed as a percentage.